A case study on intergenerational knowledge transfer strategies / Suhada Surani - Surani, Suhada (2014)
In managing knowledge management there are three process, knowledge acquisition, knowledge transfer and knowledge sharing. All the processes are related to each other. While having the changing world from traditional to technology, baby boomers generation started to retire and need to share and transfer their knowledge to the next generation. Family business is a one characteristic that shows the inter generational element. Consequently it will happen with the intergenerational knowledge transfer while they sharing their knowledge. Hence, this research is tends to gather and analyze the intergenerational knowledge transfer strategies and proposed a suitable technology in intergenerational knowledge transfer strategies which scope on doing this research are family business. Knowledge transfer strategies consist of knowledge type, knowledge transfer tool and mechanism also the knowledge transfer recipients. The motivations of the knowledge transfer are basically from the individual itself. This qualitative interpretive research is based on the purposive method in order to gather data through interview with three family businesses selected around Malaysia. Then, the conceptual analysis is used to structure the data from interviews. From the data analysis and finding in this research, knowledge type, knowledge transfer tools and recipients are identified and a technological element in knowledge transfer strategies are being proposed as achieved the objectives of the research based on current strategies used and literature review that researcher has gone through. Intergenerational knowledge transfer also give a lot of benefit to communities because with the knowledge that had been transfer can be absorb and use wisely in life.